The Self-Orientalization of Polish Music Education - Switala, Adam (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Polish and international scholars have frequently made use of the postcolonial lens as a presumably valid tool to examine conditions in post-soviet Eastern Europe. The mutual Orientalization of the “other” during the Cold War period in both democratic and communist camps appears to have occasioned prevailing after-effects in the field of Polish music education. This article discusses the above thesis in relation to the writings of two highly influential representatives of postcolonial thought who are also personally connected to the world of music: Edward Said and Rabindranath Tagore. Sections one and two explain the use of the concept of Orientalism as an analytical framework for the article and briefly discuss the rationale behind looking at Poland as a postcolonial country. Next, selected articles by Polish scholars are being analyzed with regard to the historical context of music education in Poland and a broader international perspective. The contemporary discourse of Polish educational policymakers is being discussed with regard to the underlying philosophical and ideological approaches. Finally, the article emphasizes some of the main issues preventing the system of general music education in Poland from acquiring a more inclusive and democratic framework and proposes possible future directions for sustainable change.